Promoting Sustainable Urban Farming Through Plant Clinic Consultations on Car Free Days - Norbertus Citra Irawan; Haryuni; Tyas Soemarah Kurnia Dewi; Sapto Priyadi; Suswadi (Journal of Community Capacity Empowerment, 2023)
In the face of rapid urban growth, this community service activity addresses the problem of decreasing green open land and the lack of awareness of sustainable agriculture. Activities carried out during the car-free day on Jalan Slamet Riyadi, Surakarta, involved a plant clinic, demonstrations of sustainable maintenance and distribution of seeds. The aim is to increase the understanding of urban communities about the importance of sustainable agriculture and provide practical guidance. Through direct interaction with experts and hands-on practice, these activities increase people's understanding and confidence in caring for plants. The distribution of seedlings also stimulates interest in gardening and an increase in greenery. The results of this dedication encourage active participation in urban farming, providing benefits to the environment and the community's quality of life. This activity confirmed that direct approaches with communities, through clinics, demonstrations, and active participation, effectively address urban environmental challenges and raise awareness of sustainable agriculture.